Determination of Three Endocrine Disruptors in Water Samples by Ultrasound-Assisted Salt-Induced Liquid-Liquid Microextraction (UA-SI-LLME) and High-Performance Liquid Chromatography – Diode Array Detection (HPLC-DAD). (2nd January 2022) - Rozaini, Muhammad Nur' Hafiz; Saad, Bahruddin; Yahaya, Noorfatimah; Lim, Jun Wei; Mohd Aris, Muhammad Naeim; Ramachandran, Muggundha Raoov
Abstract: Endocrine-disrupting compounds are routinely detected in environmental water. In this study, a simple and rapid sample preparation method based on ultrasound-assisted salt-induced liquid-liquid microextraction (UA-SI-LLME) followed by high performance liquid chromatography – diode array detection (HPLC-DAD) was developed for the determination of triclosan, triclocarban and methyl-triclosan in water. Parameters that affect the extraction efficiency – such as type and mass of salt, type and volume of extraction solvent, extraction time, sample pH and sample volume – were studied. Under the optimized conditions, the method demonstrated linearity from 0.18 to 1000 µg L −1 with coefficients of determination R 2 ≥ 0.9899, limits of detection from 0.05 to 0.2 µg L −1, and good recoveries (> 70%) with relative standard deviations < 10%. The method was applied for the determination of triclosan, triclocarban, and methyl-triclosan in swimming pool, lake, and wastewater. The greenness of the method was quantified using the Analytical Eco-Scale Index.